The Impact of Rumors on the Saudi Economy with Reference to the Stock Market - Meteb, Alotaibi Mohamed (Journal of Ecohumanism, 2024)
The economic field is considered as the most affected field of rumors because it is related to individuals’ daily standard of living and other issues such as: inflation, unemployment, subside, taxation, salaries, wages, bonuses, stock markets and foreign investment, etc. This paper aims to identify concept, characteristics and conditions necessary for rumors success, in addition to identify the reasons, motives, types, sources and means of rumors spread with displaying some examples and models of the most important rumors which have been recently launched and have negative economic effects on the Saudi economy, especially the stock market. The paper also aims to explain the role of rumors in the Saudi stock market crisis, the occurrence of the financial bubble, and the stock market collapse on February 26, 2006. The analytical and descriptive approach was adopted through the description of various rumors phenomenon. The results of the paper also indicated that the environmental and social level plays an important role in the spread of rumors. As the cultural and educational level decreases, rumors increase, and vice versa. The paper pointed out the impact of rumors on the Saudi stock market, which the stock market is one of the most affected economic sectors by rumors that target affecting the investors’ confidence in the financial markets. The launching of such rumors negatively affects the stock market stability. The paper recommended responding quickly to the rumor because failure to respond means proving and confirming the rumor. It also recommended activating government oversight and monitoring of stock market transactions to ensure the accuracy and transparency of information, imposing deterrent and penalties on rumors promoters in the stock market.